The Systemic Effect of Burn Injury and Trauma on Muscle and Bone Mass and Composition. Issue 5 (November 2015) - Rinkinen, Jacob; Hwang, Charles D.; Agarwal, Shailesh; Oluwatobi, Eboda; Peterson, Jonathan; Loder, Shawn; Brownly, Robert C.; Cummings, Timothy; Cederna, Paul S.; Levi, Benjamin
Abstract : Background: By understanding the global inflammatory effects on distant myopathies, surgeons can better guide the rehabilitative process for burn patients. The authors tested the systemic effect of burn injury on distant injured muscle and native bone using immunohistochemistry and validated a new morphometric analytic modality to reproducibly quantify muscle atrophy using computed tomographic imaging. Methods: In vivo studies were performed on C57/BL6 mice using an Achilles tenotomy with concurrent burn injury model. Total muscle and bone (tibia and fibula) volume/density were quantified near the site of Achilles tenotomy using micro–computed tomography at 5, 7, and 9 to 12 weeks after surgery. The impact of burn injury on the inflammatory cascade [nuclear factor (NF)-κB, p-NF-κB] and the interconnected protein catabolism signaling pathway (Atrogin-1) was assessed by immunohistochemistry. Results: Muscle volume and density at the site of Achilles tenotomy in burned mice were significantly diminished compared with nonburned mice at 5 weeks and 9 to 12 weeks. Similar decreases in muscle volume and density were observed when comparing tenotomy to no tenotomy. Cortical bone health remained stable in burn/tenotomy mice compared with tenotomy. Muscle atrophy was associated with up-regulation of p-NF-κB, NF-κB, and Atrogin-1 assessed by immunohistochemistry. Conclusions: Burn injury significantly decreases muscle volume and density. Increased muscle atrophy using our computed tomographic morphometric analysis correlated with a significant increase in intramuscular inflammatory markers and proteolysis enzymes. This study demonstrates a unique characterization of how burn injuries may worsen local myopathy. Moreover, it provides a novel approach for quantifying muscle atrophy over an expanded period. Abstract : Supplemental Digital Content is available in the text.